Delayed Diagnosis of Iatrogenic Bladder Perforation in a Neonate - Antoinette S. Birs; Jose A. Perez; Mark A. Rich; Hubert S. Swana (Case Reports in Urology)
Iatrogenic bladder injuries have been reported in the neonate during umbilical artery/vein catheterization, voiding cystourethrogram, urinary catheterizations, and overwhelming hypoxic conditions. Patients with iatrogenic bladder perforations can present with acute abdomen indicating urinary peritonitis, septic-uremic shock, or subtle symptoms like abdominal distension, pain, hematuria, uremia, electrolyte imbalances, and/or difficulty urinating. The following neonatal case report of perforated bladder includes a review of the signs, symptoms, diagnostic tools, and management of bladder injury in neonates.